Gender-based violence among people with disabilities is a neglected public health topic - Fredinah Namatovu; Raman Preet; Isabel Goicolea (Taylor & Francis Group, 2018)
This paper aims to provide an analytical insight on the current state of knowledge on gender-based violence among people with disabilities, a topic where the level of data is relatively low. We briefly discuss the current research on: (a) the prevalence, risk factors and the theoretical approaches for gender-based violence among people with disabilities. (b) Service provision among people with disabilities who experience gender-based violence. (c) We also highlight areas where further research is required, the applicable theoretical approaches and provide an example on how Sweden is attempting to bridge this knowledge gap through implementing the Disability and Intimate-partner violence project (DIS-IPV) project.